First Identification of Phospholipase C (PlcH) Gene in Multi-Drug Resistant Acinetobacter baumannii Isolated from Clinical Specimens in Iraq - Abdulsadah, Bushra Ghanem; Hadi, Zainab Jaber (Medical Science Journal for Advance Research, 2024)
Background: Acinetobacter baumannii is gram negative opportunistic bacteria increasingly associated with various epidemics,representing a serious concern according to the broad spectrum of antimicrobial resistance and clinical manifestations ,with high mortality rates, especially in patients who reside in intensive care units. Objective: The current study aimed to molecular detection of PlcH gene and other virulence genes. Subjects and methods: Cross-sectional study was conducted for five months, starting in September 2023 and finishing in January 2024. Two esteemed establishments, Baghdad Teaching Hospital and Al-Sadder Medical City, located in the provinces of Baghdad and Najaf, respectively, provided a total of sixty-five clinical samples. The samples were put through a thorough processing technique that comprised morphological approaches, biochemical tests, and Vitek2 systems to ensure the accuracy of the diagnosis. 22 distinct antibiotics from 9 antimicrobial groups had their susceptibility to antibiotics assessed. For the colistin antibiotic the Colistin Broth Disk Elusion Method was used and the disk diffusion method for other antibiotics.Conventional PCR analysis using monoplex and multiplex techniques is utilized to identify particular virulence genes .Result: The investigation involved the examination of 65 specimens obtained from patients ,which included of sputum 31(47.6%), burn exudate 11(16.9%), wound abscesses 8(12.3%) and blood 7(10.7%), buccal swab 4(6.1%), urine 3(4.6%) , pus 1(1.5%) from the total .The majority of the specimens were collected from hospitalized patients 55 (84.6%) ,while there10 (15.3% )indicating a substantial contrast in comparison to outpatients .The rates of resistance were as follows: Ampicillin and Pipracillin (100%) ,Ampicillin-sulbactam(95%), Pipracillin tazobactam (91%), Ticarcillin clavulanic acid (92%). Ceftazidime (95%), Cefotaxime, Ceftriaxone and Cefepime (100%), Imipenem (98%), Meropenem (92%), Amikacin (98%), Gentamicin (91%), Tobramycin (77%), Netilmicin (55%), Doxycycline (40%), Minocycline (20%), Ciprofloxacin (94%), Levofloxacin (92%), Gatifloxacin (28%), Trimethoprim/sulfamethoxazole (92%), Colistin (71%). PCR amplification revealed the following genes bla OXA-51 52(80%), 4(8%) of isolates was positive for the presence of PlcH gene,Omp-A 47(90%) and Bap 19 (37%), FimH 13(25%), FimA(0%), epsA 19(37%), ptk 11 (21.1%). Conclusions: A higher percentage of A.baumannii isolated from sputum samples. High rates of biofilm formation genes (Omp-A and Bap), followed by capsular polysaccharide genes (EpsA, ptk), Adherence genes (FimH) and FimA was not detected. Tissue destruction gene (PlcN), First reporet of phospholypase gene (plcH) in Iraq.